1997
DOI: 10.1016/s0925-4773(97)00672-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of a novel mouse gene with sequence similarity to the Drosophila fat facets gene

Abstract: The Drosophila fat facets (faf) gene is a ubiquitin-specific protease necessary for the normal development of the eye and of the syncytial stage embryo in the fly. Using a gene trap approach in embryonic stem cells we have isolated a murine gene with extensive sequence similarity to the Drosophila faf gene and called it Fam (fat facets in mouse). The putative mouse protein shows colinearity and a high degree of sequence identity to the Drosophila protein over almost its entire length of 2554 amino acids. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 21 publications
1
69
0
Order By: Relevance
“…Given the high levels of FAM expression in epithelia during development (Wood et al, 1997;Kanai-Azuma et al, 2000), the identification of ␤-catenin and AF-6 as substrates (Taya et al, 1998(Taya et al, , 1999 and the loss of blastomere adhesion after depletion of FAM (Pantaleon et al, 2001), we decided to further investigate FAM function in epithelia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high levels of FAM expression in epithelia during development (Wood et al, 1997;Kanai-Azuma et al, 2000), the identification of ␤-catenin and AF-6 as substrates (Taya et al, 1998(Taya et al, , 1999 and the loss of blastomere adhesion after depletion of FAM (Pantaleon et al, 2001), we decided to further investigate FAM function in epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo depletion of FAM in preimplantation mouse embryos, by addition of antisense oligonucleotides, resulted in a parallel decrease in ␤-catenin. AF-6 levels were also initially reduced but returned to normal; however, the nascent protein was mis-localized to the apical surface of blastomeres (Pantaleon et al, 2001).Given the high levels of FAM expression in epithelia during development (Wood et al, 1997;Kanai-Azuma et al, 2000), the identification of ␤-catenin and AF-6 as substrates (Taya et al, 1998(Taya et al, , 1999 and the loss of blastomere adhesion after depletion of FAM (Pantaleon et al, 2001), we decided to further investigate FAM function in epithelia. …”
mentioning
confidence: 99%
“…USP9X is a USP domain-containing DUB that was initially identified as a human homolog of Drosophila fat facets (faf) gene (19). Recent studies have reported that USP9X plays important role in the regulation of cell survival and TGF-β signaling by deubiquitinating myeloid leukemia cell differentiation protein 1 (Mcl1), Itch, and Smad4 (20)(21)(22); however, the function of USP9X in the immune system, particularly in T-cell regulation, remains unknown.…”
mentioning
confidence: 99%
“…In addition, the large number of Ubp family members and the fact that dierent Ubps do not show signi®cant homology outside of their active catalytic sites also suggest a speci®city of interaction with de®ned substrates. A murine homolog of Faf termed Fam (fat facets in mouse) was isolated from embryonic stem cells (Wood et al, 1997). Several potential substrates for Faf/Fam have been suggested, including Af-6, epsin and b-catenin (Cadavid et al, 2000;Isaksson et al, 1997;Kanai-Azuma et al, 2000;Taya et al, 1998Taya et al, , 1999.…”
Section: Tinmentioning
confidence: 99%